The Development of Learner Network Society Skills by Technology Subject Teachers in the Gauteng Full ICT Schools - Shindiri, Charlotte Dineo (University of the Witwatersrand, Johannesburg, 2024)
The issue of teacher utilization of Information and Communications Technologies (ICTs) confidently and creatively, to help South African learners develop the skills and knowledge they need, has been debated extensively. This is essential for learners to achieve their personal goals and become full participants in the global community. Although the National Curriculum Assessment Policy Statement (CAPS) envisions the utilisation of ICTs for teaching and learning in each subject, it is silent on the pedagogical approaches for learners to acquire the desired ICT skills to participate meaningfully in the global community. Instead, the literature reviewed has revealed that teachers are utilising the available ICT resources deployed in schools mainly for content acquisition. Teachers offering Technology in Gauteng Full ICT schools also fall within this category. The Grade 8 Technology CAPS curriculum is also silent on using ICTs to solve the real-life problems identified. In an attempt to ensure that South Africa does not fall victim to a ‘digital divide’, the ICT resources deployed in these schools need to be utilised effectively to develop the necessary knowledge and skills for learners to compete successfully in the global world. Accordingly, teachers in these schools have been capacitated to use ICT resources to enhance the quality of teaching and learning. However, the studies conducted to establish the return on investment in the ICT resources deployed in schools have revealed a mismatch between the desired educational outcomes and what is prevailing on the ground at the implementation level. This study focused on understanding how Grade 8 Technology teachers from the Full ICT schools in Gauteng utilise the available ICT resources during teaching and learning activities to create opportunities for learners to acquire the ICT skills required to solve the identified real-life problems in Technology and participate meaningfully in the global world. The findings assist in the development of an ICT Teacher Development Framework that guides teachers on how to utilise the available ICT resources to facilitate teaching and learning activities in sync with the South African Education Policy (the CAPS document) aspirations. The study used a multiple case study design that relied on semi-structured interviews, classroom observations, lesson plans and social media use to understand the development of Learner Network Society Skills (LNSSs) by the Grade 8 Technology teachers in four Full ICT xiv schools in Gauteng. This aimed to customise the findings to facilitate the development of the desired ICT skills, considering the South African context. The study adopted Connectivism as the main learning theory to understand how teachers could equip learners with network society skills. Since this theory is not wholly suitable for teaching and learning in the South African context, the developed Guided Blended Connectivist Learning Framework became instrumental in achieving this goal. It employs four learning frameworks to merge traditional face-to-face teaching and learning with online learning to help identify teaching and learning activities that facilitate the development of LNSSs in the context of the Full ICT schools in Gauteng. The results reveal the conditions that support the development of the desired ICT skills in these schools. It is recommended that the current content-heavy Grade 7 - 9 Technology curriculum be reviewed, to incorporate the pedagogy and LNSS to be acquired, as learners engage in the standard technological design process, to address real-life problems.
A research report submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Network Society Skills; Connectivist Learning; Blended Learning; Modelling; Problem-Based Learning; SDG-4: Quality education